(untitled) (American Journal of Islam and Society, 2010)
Emma Williams is a British doctor who studied history at Oxford and medicine at London. This book, which was first published in Britain in 2006, records her experiences and assessments of what she saw when she accompanied her husband, a senior UN official, to Israel during 2000-03. The family lived in Jerusalem’s “Forest of Peace,” an area south of the old city, which remained undeveloped because it had been no man’s land patrolled by the UN between 1948 and 1967. Emma and her husband went with three children and had a fourth, born out of choice in a Palestinian hospital in Bethlehem, while they were there. Her husband spent much of his time in Gaza; Emma worked in Jerusalem and, when possible, in the West Bank ...